Communication Source of Seeking Health Information among Women: A Study in Orerokpe, Delta State, Nigeria - Akpoghiran, Idamah Patrick (NIU Journal of Social Sciences; Vol 6 No 1 (2020): KIU Journal of Social Sciences, Vol. 6 No. 1, March 2020, 2020)
Through different communication sources, people seek health information for various reasons. Health information is important for people to understand their health situations and how to go about it. The study examines communication source of seeking health information among women in developing countries. The main objective of the study was to determine the communication source of seeking health information among women. The scope of the study was Orerokpe, a semi-urban town in Delta state, Nigeria. Substantial literatures on health-seeking information were reviewed. The study was anchored on the Wilsonâ€™s theory of information seeking behaviour, which explains that people seek information in order to satisfy some information needs. A total of three hundred and thirty-eight (338) women between the ages of 20 to 65 years were surveyed using the instrument of the questionnaire. The study among others showed that the internet is a major communication source for seeking health information on regularly basis among educated women in developing countries but for clarity and complexities of health-care service and information, medical practitioners, pharmacists and nurses were sources of health-seeking information. The study also showed that while participants access health information but only consult a medical practitioner when it is a serious case.   It should be noted that frequent seeking for health information reduces uncertainty regarding health status and help to improves lives. Keywords: Communication source; health; health-seeking information; information; women